STUDI EKPERIMENTAL PENGARUH PROSES GALVANISASI CELUP PANAS (HOT DIP GALVANIZING) TERHADAP KUAT TARIK BAJA RINGAN - misdi, misdi (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
This study examines the effect of galvanization on the tensile strength of light steel widely used in civil construction. The zinc coating process (galvanization) on light steel aims to protect it from corrosion. Galvanization provides a protective zinc layer that prevents corrosion damage to the light steel. However, the high temperatures involved in galvanization can affect the mechanical properties of the steel. The research method involved tensile testing on C-profile light steel samples, both with and without galvanic coating. Test results showed that for light steel with a thickness of 0.45 mm, galvanization caused a 9.51% decrease in tensile strength. For steel with a thickness of 0.75 mm, tensile strength decreased by 6.54%. Meanwhile, for relatively thicker light steel at 1.00 mm, the tensile strength dropped by 2.65% compared to uncoated steel. This study confirms that while galvanization enhances corrosion resistance, it may reduce the mechanical performance of light steel, especially in thinner sections.